PENGGUNAAN METODE LATIHAN UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MEMBACA TEKS DESKRIPTIF DI KELAS VII SMP BAITURROSYID - ERA ASTATI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2023)
This Classroom Action Research (CAR) is motivated by the low ability of students to read descriptive texts in English subject. The formulation of the problem in this study is how is the application of the training method in improving students' ability to read descriptive texts in English in class VIII SMP Baiturrosyid Padang. In order for this classroom action research to work well without obstacles that interfere with the smooth running of the research, the researcher compiled the stages that were passed in the classroom action research, namely: 1) Action planning/preparation, 2) Action implementation, 3) Observation, and 4) Reflection. The successful application of the exercise method to English subjects was known from the increase in students' ability to read descriptive texts from before the action, cycle I, and cycle II. Before the action, students' ability to read descriptive texts was classified as